2020
DOI: 10.1038/s41598-020-76884-8
|View full text |Cite
|
Sign up to set email alerts
|

The burden of anthropometric failure and child mortality in India

Abstract: The public health burden of nutritional deficiency and child mortality is the major challenge India is facing upfront. In this context, using National Family Health Survey, 2015–16 data, this study estimated rate of composite index of anthropometric failure (CIAF) among Indian children by their population characteristics, across states and examined the multilevel contextual determinants. We further investigated district level burden of infant and child mortality in terms of multiple anthropometric failure prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
4
18
2
1
Order By: Relevance
“…The finding of this study indicated that children whose mothers are thin (having a BMI below 18.5) had more anthropometric failures as compared to children whose mothers had normal body weight (BMI 18.5-24.95). This finding is in line with other studies conducted in sub-Saharan Africa [ 16 , 33 ] and India [ 17 ]. This group consists of more at-risk population segments for children anthropometric failure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding of this study indicated that children whose mothers are thin (having a BMI below 18.5) had more anthropometric failures as compared to children whose mothers had normal body weight (BMI 18.5-24.95). This finding is in line with other studies conducted in sub-Saharan Africa [ 16 , 33 ] and India [ 17 ]. This group consists of more at-risk population segments for children anthropometric failure.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that childhood anthropometric failures are significantly associated with maternal and paternal education. Previous studies conducted have shown that maternal education has a positive effect in decreasing childhood anthropometric failure [ 16 , 17 ]. The knowledge that mothers acquire from formal education could help them to adopt essential nutrition and hygiene behaviors that may prevent children anthropometric failures.…”
Section: Discussionmentioning
confidence: 99%
“…The nding of this study indicated that children whose mothers are a thin BMI below 18.5 had more anthropometric failures as compared to children whose mothers had normal body weight BMI 18.5-24.95. This nding is in line with other studies conducted in sub-Saharan Africa [11,26] and India [15]. This group consists of more at-risk population segments for children anthropometric failure.…”
Section: Multilevel Analysissupporting
confidence: 92%
“…We also found that childhood anthropometric failures is signi cantly associated with maternal education. Previous studies conducted have shown that maternal education has a positive effect in decreasing childhood anthropometric failure [11,15]. The knowledge that mothers acquire from formal education could help them to adopt essential nutrition and hygiene behaviors that may prevent anthropometric failures.…”
Section: Multilevel Analysismentioning
confidence: 99%
See 1 more Smart Citation